CULTURAL DISCOUNT: BREAKTHROUGH POINT OF CHINA'S TV DRAMA EXPORTS TO SOUTHEAST ASIA - Li, Lingxing (International Review of Humanities Studies, 2025)
Driven by China's "Going Global" strategy, the international influence of Chinese TV series continues to grow. As a key vehicle of China's cultural soft power, these TV series have significantly bolstered China's global cultural presence, particularly in Southeast Asia, by showcasing China's rich history and contemporary societal changes. Despite certain geographical and cultural similarities between China and Southeast Asia, cultural differences still present challenges to the dissemination of Chinese TV dramas, particularly in areas such as language, values, and religious beliefs. This paper not only analyzes effective strategies for mitigating "cultural discounts" but also challenges the traditional one-dimensional view of cultural discount theory by examining the success of Chinese films and TV dramas currently popular in Southeast Asia. In fact, the influence of cultural discounts in this region is relatively minor, demonstrating that Chinese culture can achieve broader recognition and resonance in the Southeast Asian market through targeted adaptation and localization strategies.